PENGUKURAN DAN PENGENDALIAN KINERJA SUPPLY CHAIN MANAGEMENT DENGAN METODE SUPPLY CHAIN OPERATION REFERENCE (SCOR) DAN ANALYTICAL HIERARCHY PROCESS (AHP) DI PT.XYZ - Laily Qodariah (2021)
PT. XYZ is a manufacturing company that produces electric heating elements. This company has never carried out a comprehensive performance measurement so that the company often experiences problems in the planning, procurement, production, and delivery processes. Therefore, it is necessary to evaluate the performance to determine the performance of the supply chain by using the Supply chain operation reference (SCOR) method. The measurement is carried out in several stages, namely identification of the SCOR matrix, verification of Key Performance Indicators (KPI), weighting using the Analytical Hierarchy Process (AHP) method and calculation of normalized values. According to the results of the study, the supply chain flow performance value obtained was 74.12 in the good category. However, there are still several performance indicators that are a priority for improvement, that is the accuracy of planning raw material requirements, the ability of suppliers to meet demand for raw materials, the number of defective products and the number of complaints from consumers. By making improvements to these indicators, it is expected to help improve supply chain performance in the company. Keywords: Performance Measurement Supply Chain Operations Reference (SCOR), Analytical Hierarchy Process (AHP).